A Systematic Review of the Effects of Physical Activity on Specific Academic Skills of School Students - Irineu Loturco; Natalia P. Montoya; Marina B. Ferraz; Vanderson Berbat; Lucas A. Pereira (MDPI AG, 2022)
This systematic review examined the effects of distinct physical activity interventions on the academic achievement of school students based on an analysis of four distinct outcomes: mathematics, language, reading, and composite scores. This study was performed in accordance with the PRISMA guidelines and the QUORUM statement. A literature search was conducted using the PubMed-MEDLINE, Scopus, and Web of Science databases. Peer-reviewed studies published in English, Portuguese, and Spanish were considered. A random-effect meta-analysis was employed to determine the effect of interventions on academic performance. The effects between interventions and control groups were expressed as standardized mean differences. Thirty-one studies were included in the meta-analysis based on the inclusion and exclusion criteria. The exercise programs were not capable of significantly improving language, reading skills, and composite scores. Conversely, performance in math tests increased significantly after the interventions compared with the control groups. Regarding the overall effect, a significant improvement in academic achievement was detected after physical activity programs compared with controls. In conclusion, the positive effects of school-based physical education on academic performance are not uniform and may be higher for math skills. The implementation of evidence-based exercise programs in school settings emerges as a promising strategy to increase overall academic achievement in school-aged students.